Generics and Frequency Adverbs as Probability Judgments - Cohen, Ariel (Proceedings of the Amsterdam Colloquium, 1995)
This paper argues that several seemingly unrelated properties of generics and frequency adverbs have a single underlying cause. Generics and frequency adverbs are unbounded, they cannot be applied to temporary generalizations, and they require a regular distribution of events along the time axis. A generic may be false even if the vast majority of individuals in its domain satisfy the predicated property, whereas a frequency statement using e.g. usually would be true. Truth judgments of generics vary considerably across speakers, whereas truth judgments of frequency statements are much more uniform. These phenomena can all be accounted for if we assume that generics and frequency adverbs express probability judgments, and if, in turn, we interpret probability judgments to be statements of relative frequency in the limit.